The Analysis Of Dynamic Capabilities And Sustainable Competitiveness On Sustainable Performance In Indonesia Private Higher Education - Listia Nurjanah; Yolanda Masnita Siagian; Husna Leila Yusran; Hepy Hefri Ariyanto (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to investigate the relationship between dynamic capabilities, sustainable competitiveness, and sustainable performance in a dynamic business environment. The study used a quantitative research method using a questionnaire at private higher education in LLDIKTI Region X. From 242 existing private higher education, 162 respondent was collected. Data was analysed using SmartPLS software. The analysis consists of descriptive statistics, evaluation of measurement models, evaluation of structural models, and hypothesis testing. The results show that dynamic capabilities and sustainable competitiveness have a positive relationship. In addition, there is a positive relationship between dynamic capabilities and sustainable performance through the mediating role of sustainable competitiveness. The results also show that dynamic capabilities have a direct and indirect effect on sustainable performance, and there is a significant negative relationship between dynamic capabilities and sustainable performance. The results contribute to the novelty of strategic management literature.